Correlation of miR-125b with Treg/Th17 Cell Imbalance in Condyloma Acuminatum and Its Regulation on Autophagy of Keratinocytes: Mechanism of the effect of miR-125b on condyloma acuminate - Ma, Xinxin (Cellular and Molecular Biology, 2023)
Condyloma acuminatum (CA), a sexually transmitted disease caused by human papillomavirus (HPV) infection, the present research aims to analyze the mechanism of microRNA-125b (miR-125b) in condyloma acuminatum (CA) and its correlation with Treg/Th17 cell imbalance, the objective is to provide new research ideas for the prevention and treatment of CA in the future. The study population comprised 57 CA patients admitted between April 2020 and June 2022 (observation group, OG) and 64 concurrent healthy controls (control group, CG). The peripheral blood miR-125b and Treg/Th17 cells in all participants were detected to identify the correlation of miR-125b with CA severity and Treg/Th17 cells, and the diagnostic value of miR-125b for CA was analyzed. Then keratinocytes (KCs) from skin lesions of CA patients were isolated. Besides, autophagic proteins LC3-II and Beclin-1 in KCs were measured by Western blotting and immunofluorescence staining. miR-125b expression and Th17 cell percentage were lower in OG than in CG, and reduced gradually with the increase of CA severity, while the Treg cell percentage was higher versus CG and increased as CA worsened (P<0.05). miR-125b exhibited a positive association with Th17 cell percentage and an inverse correlation with Treg cell percentage (P<0.05). ROC analysis identified the excellent diagnostic effect of miR-125b on CA (P<0.05). In vitro, increasing miR-125b decreased the ability of KCs to proliferate, enhanced the apoptosis rate, and elevated LC3-II and Beclin-1 expression (P<0.05). In Conclusion, miR-125b, under-expressed in CA, is closely related to Th17/Treg cell imbalance, the mechanism is related to inhibiting the autophagy of KCs and promoting their abnormal proliferation.